Pollen sources foraged by domesticated stingless bee (Heterotrigona itama) reared in gelam forests of Terengganu, Malaysia - Muhammad Izzelen Izzauddin Mamat; Muhammad Faqih Luqman Fuaad; Nor Zalipah Mohamed; Shamsul Khamis; Chik Maslinda Omar; Daria Mathew Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2023)
Melittopalynological analysis is one of the principal tools used to reveal significant floral sources to bees. Gelam (Melaleuca spp.) forest provides habitat for bees and provision for high quality honey. However, the forests are declining due to anthropogenic activities which directly reduced the availability of botanical sources on which bees rely for survival. Hence, this study aimed to investigate the pollen sources preferred by domesticated stingless bees (Heterotrigona itama) reared in fragmented Gelam forests from two meliponiaries in Terengganu. The palynological analysis was carried out on pollen load foraged by the stingless bees. Thirty seven pollen types belonging to 13 plant families were collected from the pollen loads of 251 stingless bee foragers. Tiliagraphs with CONISS and rank abundance curves were used to illustrate the pollen grains preferred by H. itama. Results clearly showed that Melastoma malabathricum and Cyperus aromaticus were the most frequently visited and vital pollen sources for H. itama in the Gelam forests. Interestingly, Gelam (Melaleuca cajuputi) pollen is one of the floral sources, suggesting that Gelam is one of the preferred pollen and nectar sources for stingless bees. This study discovered a causal link between the fragmentation of Gelam forests and the low abundance of Melaleuca cajuputi pollen foraged by H. itama. Information on this dynamic is critically important for maintaining the health of bee colonies as well as for the conservation efforts of Gelam forests in Terengganu, Malaysia.